Penerapan Asas Geen Straf Zonder Schuld Dalam Penindakan Terhadap Kejahatan Penyalahgunaan Teknologi Deepfake - Hapid, Fasa Muhamad; Suntana, Ija; Royani, Muhammad Yayan (Universitas Semarang, 2024)
This research aims to find out the role of criminal law in responding to the development and abuse of deepfakes through the application of the geen straf zonder schuld principle as a basis for prosecution. Deepfakes, which are increasingly developing with the number of users continuing to grow, present various threats of abuse such as fraud, misuse of personal data, and the increasingly massive spread of hoax news which can clearly threaten the security and peace of society and this shows that it is important for the criminal law to take action against deepfake abuse. The analytical descriptive method with a normative juridical as approach was chosen to conduct this research. The novelty of this research lies in the analysis of the application of the geen straf zonder schuld principle in the context of criminal prosecution for misuse of deepfake technology, which has not been widely discussed in previous literature. The research results show that the application of the geen straf zonder schuld principle can be used as a guideline in dealing with and taking action against deepfake abuse and is supported by the Circular Letter of the Minister of Communication and Information Number 9 of 2023 concerning the Ethics of Artificial Intelligence which also makes it clearer that criminal action can be carried out. If we analyze the construction and substance of the crime, basically deepfake abuse is almost the same as criminal acts that we are familiar with and have existed before, but are influenced by and take advantage of technological developments. In conclusion, criminal law can play an adaptive role in dealing with deepfake abuse through the application of the geen straf zonder schuld principle. Penelitian ini bertujuan untuk mengetahui bagaimana peran hukum pidana dalam merespons perkembangan dan penyalahgunaan deepfake melalui penerapan asas geen straf zonder schuld sebagai dasar bagi penindakannya. Deepfake yang makin berkembang dengan jumlah penggunanya yang terus bertumbuh menghadirkan beragam ancaman penyalahgunaan seperti penipuan, penyalahgunaan data pribadi, hingga makin masifnya penyebaran berita hoax jelas dapat mengancam keamanan dan ketentraman masyarakat dan hal itu menunjukan bahwa penting bagi hukum pidana untuk melakukan penindakan bagi penyalahgunaan deepfake. Metode deskriptif analitis dengan yuridis normatif sebagai pendekatannya dipilih untuk melakukan penelitian ini. Kebaruan penelitian ini terletak pada analisis mengenai penerapan asas geen straf zonder schuld dalam konteks penindakan pidana penyalahgunaan teknologi deepfake, yang belum banyak dibahas dalam literatur sebelumnya. Hasil penelitian menunjukan bahwa penerapan asas geen straf zonder schuld bisa dijadikan pedoman dalam menanggulangi dan melakukan penindakan penyalahgunaan deepfake dan didukung oleh Surat Edaran Menteri Komunikasi dan Informatika Nomor 9 Tahun 2023 tentang Etika Kecerdasan Artifisial juga makin memperjelas bisa dilakukannya penindakan pidana. Jika dianalisa secara konstruksi dan substansi kejahatannya pun pada dasarnya penyalahgunaan deepfake hampir sama dengan tindak pidana yang telah kita kenal dan ada sebelumnya namun terpengaruh dan memanfaatkan adanya perkembangan teknologi. Kesimpulannya, hukum pidana dapat berperan adaptif dalam menangani penyalahgunaan deepfake melalui penerapan asas geen straf zonder schuld.